Structural steel fabrication practices - Shuster, John W. (McGraw-Hill, 1997)
Here's today's only commercially available information on best-practice steel technologies Many of today's welders and fabricators, largely because they learned their trade as practicing craftsmen, are handicapped by their incomplete understanding of the materials they work with. Structural Steel Fabrication Practices is the only practical reference that offers these technologists the comprehensive, hands-on guidance to steel fabrication practices that they've long needed. John Shuster, an experienced steel fabricator and gifted instructor in the field, provides complete information on structural steel materials and applications, as well as the equipment used in fabrication processes and the problems most often encountered by practitioners. Using numerous illustrations, charts, and tables, this resource sovers: Composition of steel and the changes it undergoes during welding and fabrication. Formation and preparation of steel for fabrication and joining. Correct ways of joining structural steel shapes, including why they work; Fabrication of steel frames of buildings, ships, trailers, and storage tanks. Identification of structural shapes, their weight, and the loads they can safely bear. Guidelines necessary to ensure worker safety on the job. Most common mistakes in welding repair--and how to correct them. From illustrating such joining processes as welding, bolting, and riveting to showing how welding, certification, and inspection can work hand in hand to produce ``super welders,'' this first-of-its-kind commercial reference is essential reading for all fabrication technologists who want to take full advantage of the rapid growth in the heavy steel fabrication industry.